The new lawyer : how settlement is transforming the practice of law - Macfarlane, Julie (UBC Press, 2008)
This provocative, intelligent work looks at the evolving role of lawyers, articulating legal and ethical complexities, the growth of conflict resolution, and the increasing impact of alternative strategies on the lawyer-client relationship and the legal system.